Discovering Psychology : The Science of Mind - Cacioppo, John T. and Freberg, Laura (Australia Cengage Learning, 2013)
Highlights connections within psychology as well as between psychology and other disciplines. This book offers the best science possible, including exciting new research findings likely to expand readers' understanding of psychology as a scientific field of study.
Include Glossary, References, Illustrations and Index
Keywords: Psychology